2013
DOI: 10.3174/ajnr.a3732
|View full text |Cite
|
Sign up to set email alerts
|

Intraplaque High-Intensity Signal on 3D Time-of-Flight MR Angiography Is Strongly Associated with Symptomatic Carotid Artery Stenosis

Abstract: BACKGROUND AND PURPOSE:Intraplaque hemorrhage in carotid artery atherosclerotic plaque has been shown to be a marker of risk, associated with prior and future ischemic events, and has been associated with regions of intraplaque high-intensity signal on 3D-TOF MRA.We assessed the association of intraplaque high-intensity signal determined on 3D-TOF MRA with the incidence of prior ipsilateral stroke or TIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
(42 reference statements)
2
22
1
1
Order By: Relevance
“…On the T1-weighted fat-saturated images, we observed a crescentic hyperintense signal (Fig 2A) consistent with hemorrhage. 3,4 The finding of Choi et al 1 of hemorrhage in 2 of the 4 patients for which carotid endarterectomy specimens were available is consistent with our findings on T1-weighted black-blood imaging in this patient. Axial source images from the 2D TOF image (Fig 2B) demonstrated abnormal flow-related enhancement in the area of the known web, possibly due to diminished or turbulent flow.…”
supporting
confidence: 90%
“…On the T1-weighted fat-saturated images, we observed a crescentic hyperintense signal (Fig 2A) consistent with hemorrhage. 3,4 The finding of Choi et al 1 of hemorrhage in 2 of the 4 patients for which carotid endarterectomy specimens were available is consistent with our findings on T1-weighted black-blood imaging in this patient. Axial source images from the 2D TOF image (Fig 2B) demonstrated abnormal flow-related enhancement in the area of the known web, possibly due to diminished or turbulent flow.…”
supporting
confidence: 90%
“…These include conventional T1-weighted fast spin echo, TOF MRA, or MPRAGE sequences. Several studies have used TOF sequencing to detect carotid IPH, and a routine MRA protocol without additional sequences to evaluate carotid atherosclerosis (1,5,9,15). The appearance of a halo sign around the carotid artery on the MIP of the TOF MRA was useful for the noninvasive detection of a fresh or recent carotid IPH on histologic analysis (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported an association between the presence of carotid IPH and cerebral ischemic events [25][26][27][28][29] . Hosseini et al [28] performed meta-analysis and showed a strong association between the presence of carotid IPH and recurrent cerebral ischemic events in symptomatic carotid artery stenosis (OR 12.2, 95% CI 5.5-27.1, p < 0.001), thereby suggesting that IPH is a promising predictor of future cerebrovascular events in patients with carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%